2008
DOI: 10.1002/elps.200700446
|View full text |Cite
|
Sign up to set email alerts
|

Micellar electrokinetic chromatographic screening of letrozole and its metabolite in human urine: Validation and robustness/ruggedness evaluation

Abstract: A simple, rapid, and sensitive method has been proposed and validated to directly quantify letrozole (LE) and its metabolite, bis-4-cyanophenylmethanol (ME) in urine samples (without any additional treatment) by micellar electrokinetic capillary chromatography (MEKC). In an effort to improve the selectivity and sensitivity of the method, the chemical and instrumental parameters were optimized. The best conditions were: 70 mM borate buffer (pH 9.2) and 40 mM SDS as BGE, 25 kV and 20 degrees C as working voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…At the beginning of determinations we have selected the type of background electrolyte (BGE) by checking the electrophoretic behavior of the analytes using an acidic BGE -phosphoric acid 25 mM and a basic BGE -25 mM borax. After our prelimary results we selected a 25 mM borax (pH 9.3) as BGE also taking in consideration previous electrophoretic studies [17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the beginning of determinations we have selected the type of background electrolyte (BGE) by checking the electrophoretic behavior of the analytes using an acidic BGE -phosphoric acid 25 mM and a basic BGE -25 mM borax. After our prelimary results we selected a 25 mM borax (pH 9.3) as BGE also taking in consideration previous electrophoretic studies [17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…Several capillary electrophoretic methods have been reported for determination of AIs in combination with other compounds, mainly micellar electrokinetic capillary chromatographic (MEKC) [17][18][19][20]. So far, there is no published electrophoretic method for the simultaneous determination of all three AIs selected in this research.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, we choose to start with a 25 mM phosphate buffer, an acidic background electrolyte (BGE), but the electrophoretic signal of the substance was difficult to detect (low value of area and height). A standard BGE containing 25 mM borax (pH 9.3) was than selected, taking in consideration also previous electrophoretic studies, however the disadvantage in a basic environment was that LET migrated very close to the electroosmotic flow (EOF) [16][17][18][19]. Adding sodium dodecyl sulfate (SDS) in the 25 mM borax BGE did not resolved the problem.…”
Section: A Capillary Zone Electrophoresismentioning
confidence: 99%
“…Until now, on a base of detailed literature survey, it was found that LET could be estimated along with other compounds only by MEKC [16][17][18][19].…”
Section: A Capillary Zone Electrophoresismentioning
confidence: 99%
See 1 more Smart Citation